Pengembangan Media Pembelajaran Magic Box pada Mata Pelajaran Matematika di SD Negeri 17 Rantau Bayur - Sania, Lia; Disurya, Ramanata; Hera, Treny (Indonesian Research Journal on Education, 2022)
The development of magic box media aims to produce valid, practical and effective elementary school mathematics learning media products. This study uses research and development methods (Reasearch and Development). By using the ADDIE model. Data was collected using a validation questionnaire sheet, student response questionnaire sheets and tests. The data analysis technique was carried out by using a validity analysis using a media expert validation questionnaire with an average validity value of 82.99, the assessment of material experts getting an average percentage of 84.25 very valid, and the assessment of the response questionnaire from students getting an average percentage of 85, 09 is very practical, and the results of the student test sheet test get an average percentage of 82.7 very effective. Based on the results of the development of the magic box learning media, it is feasible to be tested or used as a learning medium.